Tourism and hospitality management faculty satisfaction towards flexible learning: A cross-sectional survey from higher educational institutions in Central Luzon, Philippines - John Paul Miranda; Maria Anna D. Cruz (Universidad de Deusto, 2023)
The present study aimed to assess faculty satisfaction on the delivery of tourism and hospitality management programs in the flexible learning mode at the onset of the COVID-19 pandemic. It employed a purposive sampling design where 85 Tourism and Hospitality Management (THM) faculty members, across 27 Higher Education Institutions (HEIs) in the Central Luzon, Philippines, participated. While findings indicate that the faculty members are generally satisfied with the conduct of flexible learning in their institutions, they generally agree on items relating to having higher workloads, longer preparation time for a course, lack of human interaction by not seeing students face-to-face, lower participation of students, technical and connectivity problems, and the need to employ creativity and resourcefulness in the development of learning aids. As the better normal ushers in, flexible learning will still be implemented with the addition of limited face-to-face delivery. As such, faculty members play a vital role in the success of program delivery. That is, when they are satisfied with their conditions, students perform better which leads to better learning and outcome. Effective institutional support services are thus key to ensuring quality flexible learning environments. For continuous improvement, recommended actions should constantly be reviewed, modified, and enhanced to respond to uncertainties and the changing times. HEIs need to recalibrate their curriculum grounded on a deeper understanding of flexible learning to address these challenges; capacitate the faculty with innovations available to enhance student engagement; upgrade infrastructure designed to provide timely feedback and to ease out connectivity issues; and lastly, review policies on faculty workload and number of preparations to consider longer preparation time. Received: 29 December 2021 Accepted: 8 March 2023